Affirming African Identity in African American Literary Projects - McCoy-Deh, M.; Atobrah, D. (My University, 2019)
Identity Affirmation is the agenda my research, writing and teaching follow. In academic and practice presentations and publications, revelation of and intentioned expression of identity is at the core of my work. Focusing on three literary projects grounded in African identity, the transformative power of identity affirmation holds true for the struggle and evolution of the main character experiences in the co-authored novel The Search for Susu (2015). The protagonist seeks and ultimately affirms her distinct, and juxtaposed identities as both a professional scholar and as a woman of the African Diaspora. The bourgeoning expression and affirmation of cultural identity in the children’s stories, Akofa (2016) resonate as declarative assertions of self, as the main character defines, spells or offers the meaning of her name in each story. The fantasy novel, October Visitors (in progress) harnesses the religious beliefs of African ancestors and living dead across the Diaspora to rescue their living progeny. All of the literary projects incorporate spatial complexities of identity and place – United States and West Africa – which help to both isolate and complicate concepts of identity.
Seminar
Keywords: African Identity; United States and West Africa; juxtaposed identities; African Diaspora